Failure analysis of geothermal perforated casing tubing in H2S and O2 containing environment - Prabowo, Harris; Pratesa, Yudha; Tohari, Askin; Mudakir, Ali; Munir, Badrul; Soedarsono, Johny W. (Eastern-European Journal of Enterprise Technologies, 2020)
A failure incident occurred on perforated casing tubing for geothermal wells. The damage happened during the drilling process by an air drilling technique after eleven days from the installation. Even though air drilling is a common method for geothermal drilling, this incident showed a lesson to learn to prevent a similar accident in the future. Failure analysis based on the laboratory and field observation was done to get the failure incident's root cause. The visual identification result showed a severe depletion and cracks in the tubing at a depth of 1,450–1,500 m. Optical emission spectroscopy and the tensile test showed materials appropriateness to the specifications. The corrosion attacked from the outer side of the tube. This tubing was exposed to an environment with significant H2S, CO2, water steam, and oxygen from the air drilling process. The results of X-ray diffraction analysis (XRD) showed FeS and Fe3O4 in the corrosion product. Both of the scale formed as a different layer, where the FeS is formed below the Fe3O4 layer. The energy dispersive spectroscopy (EDS) results revealed that each tubing's sulfur content gets an increase in the deeper location. The gas sampling result showed that H2S gas is more dominant than CO2 gas, which showed the sour service condition. Corrosion rate calculation modeling was also performed based on the environment parameter; the result is lower than the real cases. The oxygen from air drilling also accelerates the corrosion rate as it acted as an oxidizing agent in the process. Free sulfur is possibly formed, which is possibly transformed into sulfuric acid. This study showed the lesson learn about the deadly combination of sulfur, oxygen, H2S, and CO2, making a severe corrosion rate in the perforated tubing